Behavior-psychological linkages: how health literacy enhances life satisfaction in Chinese university students through the mediation of persistent exercise and emotional management ability - Zuo, Hao-jie; Liu, Ting-ting; Zhang, Ding-you; Xu, Yu-cai; Lou, Hu; Han, Shan-shan; Yu, Shi-hai; Li, Bo (Frontiers in Psychology, 2026)
ObjectiveThis study investigates the associative mechanism between health literacy and life satisfaction among university students in China, specifically examining the chain mediation pathway involving persistent exercise and emotional management ability. Health Literacy is understood as the capacity of an individual to access, comprehend, appraise, and utilize relevant health information to promote and maintain well-being proactively. Complementing this is the concept of Life Satisfaction, which denotes an individual’s subjective assessment of their overall circumstances and quality of life. Furthermore, Persistent Exercise refers to the sustained and regular engagement in physical activity necessary for long-term physical conditioning. Finally, Emotional Management Ability—often framed as emotional intelligence—is the aptitude for an individual to effectively recognize, understand, modulate, and appropriately deploy their affective states. It explores the chain-mediated roles of persistent exercise and emotional management ability. Considering persistent exercise as a behavioral factor and emotional management ability as a psychological factor, this research aims to provide a theoretical basis for enhancing the quality of life of university students by investigating the chain-mediated effects of these factors.MethodsThis research constitutes a cross-sectional investigation. Data collection was standardized across administrative classes in September 2024, facilitated through the Wenjuanxing survey platform. A multi-stage stratified cluster sampling method was employed to select 16,395 university students across five provinces in China. The sample size was determined through proportionate allocation, benchmarked against the total national population of university students. A minimum sample size of 45 participants was required for each stratum—subgroups defined by gender and academic year/grade level—to achieve the necessary statistical power for the analysis. Measurements were operationalized using the Health Literacy Scale (HLS-SF9), the Satisfaction with Life Scale (SWLS), a scale for measuring exercise adherence, and the Emotional Intelligence Scale (EIS). Statistical analyses were conducted utilizing SPSS Version 26.0, the PROCESS macro (Version 4.2), Microsoft Excel, and MATLAB. The methods employed included descriptive statistics, correlation analysis, and regression analysis.ResultsHealth literacy was significantly positively correlated with life satisfaction (β = 0.184, p < 0.001). Persistent exercise and emotional management ability appeared to act as chain mediators in the relationship between health literacy and life satisfaction, with a total effect of 0.506 (95% CI [0.486, 0.525]), a total direct effect of 0.183 (95% CI [0.164, 0.203]), and a total indirect effect of 0.322 (95% CI [0.306, 0.338]). Specifically, health literacy demonstrated a positive association with life satisfaction (β = 0.090, p < 0.001; β = 0.520, p < 0.001), as it both enhanced persistent exercise (β = 0.952, p < 0.001) and improved emotional management ability (β = 0.277, p < 0.001). The chain-mediated pathway “Health literacy → Persistent exercise → Emotional management ability → Life satisfaction” had an effect of 0.092 (95% CI [0.085, 0.099]).ConclusionThis study revealed a significant association between health literacy and life satisfaction among Chinese university students. Furthermore, persistent exercise and emotional management ability were found to be potentially associated with both life satisfaction and health literacy, suggesting possible indirect pathways.